Coping Techniques and Family Empowerment in Lowering Diabetes Distress, Depression, and Personal Care Management Among Individuals Having Diabetes Type 2 Kahuripan Health Centre Working Area, Tasikmalaya City - Anih Kurnia; Betty Suprapti; Aruf Khoerun Nufus; Gilang Ramadan; Raihan Thoriq Abdillah; Rillah Arti Utami (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Diabetes is a problematic condition that must be controlled effectively. Adaptive coping methods are techniques for dealing with situations or stressors that require someone to handle them. Problem-focused coping strategies attempt to modify the source of stress, whereas emotional emphasis focuses on regulating the feelings that arise in response to perceived stress triggers. This study explores coping strategies and family empowerment for improved self-care management in persons with type 2 diabetes. This community service used a descriptive quantitative design using a total sampling technique, which included all sufferers who participated in PROLANIS activities between February 5 and May 27, 2024. Activities were carried out to develop an understanding of adaptive coping strategies and disease perspectives in managing the diabetes mellitus they suffer. Results. Blood pressure measurements in stage 1 hypertension fell from 38.6% to 28.1% following the activity and in stage 2 hypertension, from 26.3% to 22.8%. Body mass index (BMI) grew from 38.6% to 63.2%, overweight from 33.4% to 15.8%, and obese from 28% to 21.1%. HbA1c, total cholesterol, and triglycerides did not change with HbA1c levels > 6.5% (54.4%); total cholesterol at alert level 36.8%; danger > 240 mg/dl 28.1%; triglycerides at alert level 17.5%; danger > 400 8.8%. The Bref-Cope questionnaire revealed that the majority of respondents had strong coping in focussing (70.2%), were able to deal with emotions well (91.2%), and were able to overcome avoidance (57%). According to the research findings, most PROLANIS participants' coping techniques were effective, albeit the results varied, beginning with focusing on difficulties and overcoming avoidance. This demonstrates that most T2D patients have adapted to their illnesses. However, HbA1c, total cholesterol, and triglyceride test results show an inverse relationship. This demonstrates poor self-care management on the part of the patient. T2D patients require assistance in managing self-care through family empowerment and the active participation of patients, families, and healthcare providers in preventing complications.